Dietary Intake and Emotional Eating Status in Relation to Gestational Weight Gain among Indonesian Pregnant Women in Bantul - Sativa, Rani Risa; Aji, Arif Sabta; Yulinda, Rahmawati; Purnamasari, Sintha Dewi; Paratmanitya, Yhona (Poltekkes Kemenkes Palu, 2023)
Introduction: Covid-19 pandemic impact the ability to reach nutritious food due to social restrictions and economic difficulties situation. Objective: This study determined the relationship between dietary diversity status (DDS) and emotional eating and its association with dietary intake and gestational weight gain (GWG) in Bantul, Indonesia. Methods: The cross-sectional study design conducted from December 2021 to February 2022 in three public health centers. Of 105 third trimester pregnant women were obtained and interviewed for DDS, semi quantitative food frequency questionnaire (SQ-FFQ), and emotional eating questionnaires. Bivariate analysis was used to measure association between variables with SPSS 25.0 version. Results: The majority of pregnant women had an adequate varied diet and an emotional eating with food (59.0% and 56.2%, respectively). The GWG status was mostly (61%) had normal GWG. There was no association of DDS with GWG (p = 0.131). However, there was a significant association between emotional eating and dietary intake status on GWG status (p<0.001 for all comparisons). Conclusion: Dietary intake and emotional eating during pregnancy were linked to GWG status. Pregnant women need to maintain their psychological well-being and dietary intake in order to maintain a normal GWG and prevent adverse pregnancy outcomes.